PERSONALITY TRAITS, MOTIVATIONAL ORIENTATIONS AND SPEAKING ACHIEVEMENT IN THE EFL CONTEXT - Arniatika, Sefvirda (Sanata Dharma University Yogyakarta, 2020)
Despite the fact that a number of studies have shown a relationship between personality traits (extrovert and introvert) with oral performance in the EFL setting, the link between extrovert and introvert personality, EFL motivational orientations, and speaking achievement is very rare. Therefore, this present study aims to find what differences are truly existed between extrovert and introvert personality regarding to their motivational orientations and speaking achievement, and how extrovert and introvert personality are inter-correlated with EFL motivational orientations and speaking achievement. In order to identify the students’ personality, the researcher used The Eysenck Personality Questionnaire (EPQ) and Self-Report Questionnaire to identify the students’ motivational orientations. The samples of this study are 40 students in XII grade of Senior High School in East Lampung, Indonesia. The data is further analyzed by using Independent samples T-test and Pearson product moment correlation coefficient. The results show that there is no significant difference between extrovert and introvert personality in both their motivational orientations and speaking achievement. Moreover, it is also found that there is a combination of motivational orientations that co-exists in the extrovert personality. However, both personality traits and motivational orientations are not supposed to be a strong predictor of students’ speaking achievement. Therefore, this present study is largely extended to give a plausible explanation to the field under investigation.DOI: 10.24071/ijiet.2020.040109